Performance of leaf extract media in culturing mycorrhizal mushroom mycelium - Alec Mlambo; Mcebisi Maphosa (South African Journal of Science, 2023)
In-vitro culture of mycorrhizal mushroom (MM) species in southern Africa remains largely unexplored, particularly using tree-derived media. In this study, a Julbernardia globiflora [(Benth.) Troupin] leaf infusion was tested for its ability to promote MM mycelial growth. Amanita loosii, Cantharellus miomboensis and Cantharellus heinemannianus isolates were incubated at a pH of 2, 3, 4, 5, 6 or 7 and at 25 °C in six leaf extract agar (LEA) infusion concentrations of 150, 175, 200, 225 or 250 grams of leaves/L distilled water, with potato dextrose agar (PDA) as a standard. We determined mycelium growth rates for all treatment combinations. Mycelium growth rate was found to be optimal at a pH between 4 and 6 in all leaf infusion concentrations tested. Significant (p<0.001) linear regressions of A. loosii and C. miomboensis were found for pH only (R2=0.837 and 0.8582, respectively) and a significant (p<0.001) regression was found for C. heinemannianus (R2=0.293). Amanita loosii and C. heinemannianus had faster (p<0.001) growth in PDA than in LEA, while C. miomboensis had similar growth rates in the two media. Growth characteristics observed were attributed to acid phosphatase mediated physiological processes in mycelium for the different MM species with an optimum pH of 4–6. MM mycelia were white, mycelia for A. loosii and C. miomboensis were loose and for C. heinemannianus were thin filaments. LEA proved to be a potential alternative medium for culturing MM species.